OBSTACLES FOR FOREIGN STUDENTS IN LEARNING INDONESIAN LANGUAGE - Hasna Shofiyah; R. Panca Pertiwi Hidayati; Desti Fatin Fauziyyah; Irfan Rifai (PT. Jurnal Center Indonesia Publisher, 2025)
The problems of learning Indonesian can be seen by focusing this study on teaching materials, learning processes, and cultural differences. The design of this research uses a qualitative approach with descriptive research type. The data in this research are in the form of speech containing information obtained from notes on the results of questionnaires that have been submitted to foreign students. In accordance with the research objective, namely to describe the problems of learning Indonesian for foreign students of the BIPA program. The data source in this research is the results of a questionnaire obtained from external campus activities carried out by researchers together with foreign students. The results of the research show that there are problems with foreign students when learning Indonesian. Keywords: Problems, teaching materials, learning processes, and cultural differences.